2015
DOI: 10.4103/0019-5545.161479
|View full text |Cite
|
Sign up to set email alerts
|

Women and mental health in India: An overview

Abstract: Gender is a critical determinant of mental health and mental illness. The patterns of psychological distress and psychiatric disorder among women are different from those seen among men. Women have a higher mean level of internalizing disorders while men show a higher mean level of externalizing disorders. Gender differences occur particularly in the rates of common mental disorders wherein women predominate. Differences between genders have been reported in the age of onset of symptoms, clinical features, fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 14 publications
0
87
0
5
Order By: Relevance
“…Study conducted by Panigrahi et al showed no association between family type and CMDs. 19,27,28 There was significant association with BMI and common mental disorders on univariate analysis. Similar association was seen in a study by Shidhaye et al 20 As evidenced from this study, the magnitude of common mental disorders is high among women of reproductive age group.…”
Section: Discussionmentioning
confidence: 91%
“…Study conducted by Panigrahi et al showed no association between family type and CMDs. 19,27,28 There was significant association with BMI and common mental disorders on univariate analysis. Similar association was seen in a study by Shidhaye et al 20 As evidenced from this study, the magnitude of common mental disorders is high among women of reproductive age group.…”
Section: Discussionmentioning
confidence: 91%
“…1,2 The stressed medical university environment, many times, harms the student's academic performance in their physical health and psychosocial well-being, affecting their quality of life. 3 CMD is a syndrome characterized by depressive and anxiety symptoms, irritability, fatigue, insomnia, memory, and concentration difficulty, 1,[4][5][6] which can manifest as a mixture of somatic symptoms, 5,6 like tremors, headache, poor digestion, among others. 6 The study performed with Gondar University Students in Ethiopia found a CMD prevalence of 40.9%.…”
Section: Introductionmentioning
confidence: 99%
“…They manifest as a mixture of somatic, anxious and depression symptoms (2) . Early and correct diagnosis of these disorders is fundamental to avoid physical and psychological damage to the individual and burden to the health system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, articulating mental health with the Family Health Strategy (FHS) is relevant (4) . Gender differences are present in CMD, predominantly affecting women (2,(5)(6)(7)(8) . Some Brazilian studies have shown the prevalence of CMD in women in urban areas to be: 33.8% (8) , 37.9% (6) , 41.7% (3) , 52.1% (7) .…”
Section: Introductionmentioning
confidence: 99%